Trastornos de la conducta alimentaria y su relación con la autoestima en las estudiantes de la Unidad Educativa Nicolas Infante Diaz - Suarez Layedra, Ketty Gabriela (2025)
Eating disorders (EDs) represent a significant public health challenge, especially among adolescents, who are particularly vulnerable to beauty stereotypes and the influence of social media. This study, conducted with 60 students from the Nicolás Infante Díaz Educational Unit, aimed to determine the relationship between EDs and self-esteem, using a descriptive-correlational design. The SCOFF questionnaire was used to identify the risk of EDs, and the Rosenberg Self-Esteem Scale was employed to assess self-esteem levels. The results showed that 63% of participants were at risk of developing EDs, while 50% exhibited low self-esteem, 25% medium self-esteem, and 25% high self-esteem. Furthermore, a correlational analysis revealed a weak negative relationship (-0.15094) between the two variables, suggesting that low self-esteem may be slightly associated with a higher risk of EDs, although the relationship is not significant. These findings highlight the importance of strengthening self-esteem in adolescents as a preventive strategy to reduce the risk of EDs and improve their emotional and physical well-being. Developing effective support networks and educational programs focused on promoting a positive self-image could be key interventions to address this issue.